OLFACTORY ORGAN AND ITS SEXUAL DIMORPHISM IN THE ELECTRIC RAY, NARCINE TIM LEI (DAY) - Waghray, Sarala (Indian Journal of Fisheries, 2011)
The olfactory organ of the electric ray, Narcine timlei (Day), exhibitssexual dimoi'phism. The olfactory organ, almost kidney shaped is more roundedin male, while in female it is slightly elongated and narrow. The linguiform processof lamella is more prominent in the males than in females. The olfactoryorgan in the embryo is also dealt with.